2019
DOI: 10.1136/bcr-2018-228454
|View full text |Cite
|
Sign up to set email alerts
|

Giant posterior fossa meningioma: the importance of early diagnosis and challenges concerning treatment

Abstract: Posterior fossa lesions may present with behavioural changes and/or progressive neurological deficit. Patients may have symptoms for long periods which may be attributed to other causes such as psychiatric diseases. We report a case of a 44-year-old woman with behavioural changes lasting for 5 years who lost her job, marriage and the guard of her sons. Latterly, she developed neurological deficit, hydrocephalus and intracranial hypertension. A giant left pontocerebellar angle mass was diagnosed. A retrosigmoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The study by Narayan et al [ 28 ], which was until now the largest series with 80 cases of GIMs, demonstrated that regression analysis showed age, sex, location of the tumor [ 44 , 45 ], Simpson grade of excision, and histology of tumor were the factors that significantly affected the KPS, complications, and recurrence [ 39 , 46 ]. Our series confirms just some of these findings whereas the mortality rate, recurrence rate, Simpson grade, and KPS are comparable between the two groups, but there is a higher rate of complications in the first 30 days after the surgical procedure for GIMs compared with smaller meningiomas [ 47 , 48 , 49 , 50 ]. We identified a higher incidence of postoperative ischemia, infections, and seizure in the GIM group.…”
Section: Discussionsupporting
confidence: 85%
“…The study by Narayan et al [ 28 ], which was until now the largest series with 80 cases of GIMs, demonstrated that regression analysis showed age, sex, location of the tumor [ 44 , 45 ], Simpson grade of excision, and histology of tumor were the factors that significantly affected the KPS, complications, and recurrence [ 39 , 46 ]. Our series confirms just some of these findings whereas the mortality rate, recurrence rate, Simpson grade, and KPS are comparable between the two groups, but there is a higher rate of complications in the first 30 days after the surgical procedure for GIMs compared with smaller meningiomas [ 47 , 48 , 49 , 50 ]. We identified a higher incidence of postoperative ischemia, infections, and seizure in the GIM group.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, various cases reported a higher prevalence among female patients in acquiring this ailment; some of these studies thus emphasized the most common risk factors mentioned earlier (Table 1). As for the treatment of giant intracranial meningiomas, the gold standard is total resection of the tumor, which depends on the tumor's size and location [14,15]. Table 1 highlights that the predominance of male patients diagnosed with giant malignant meningioma is extremely rare, but it predominantly affects women.…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of clinical observations, complex anatomical localization and high surgical risks suggest individual treatment planning. Anatomically, the region of Foramen Magnum is considered in the following borders: anterior -from the lower third of the clivus to the upper edge of C2 vertebra body; lateral -from the jugular tubercle of the occipital bone to the upper edge of C2 vertebra arc; posterior -from the anterior margin of the occipital bone scales to C2 vertebra spinous process [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%